An online individualised patient decision aid improves the quality of decisions in patients considering total knee arthroplasty in routine care: A randomized controlled trial. Issue 3 (September 2022) - Bansback, Nick; Trenaman, Logan; MacDonald, Karen V.; Durand, D'Arcy; Hawker, Gillian; Johnson, Jeffrey A.; Smith, Christopher; Stacey, Dawn; Marshall, Deborah A.
Abstract: Objective: The objective of this study was to evaluate the effectiveness of an online patient decision aid with individualised potential outcomes of surgery, on the quality of decisions for knee replacement surgery in routine clinical care. Design: A pragmatic Randomized Controlled Trial (RCT) in patients considering total knee replacement at a high-volume orthopedic clinic. Patients were randomized at their routine online pre-surgical assessment to either complete a decision aid or not. At their consultation, those in the intervention arm had a surgeon report summarizing the decision aid results. The primary outcome was decision quality, defined as being knowledgeable and choosing the option that matched informed treatment preferences. Multivariate logistic and linear regression analysis was conducted to consider surgeon level clustering and baseline differences between study arms. Results: Of 163 patients randomized, 155 completed post-surgical surveys and were included in the analysis. The average patient was aged 65 years, obese and had moderate to severe osteoarthritis symptoms at baseline. Patients in the intervention arm had a higher odds of making a quality decision (Odds Ratio ​= ​2.08, 95% CI: 1.08 to 4.02), predominantly through increased knowledge. Conclusions: This study supports the benefit of a decision aid in combination with a surgeon report to significantly improve decision quality in routine care. While the independent contribution of tailoring the decision aid to patient baseline characteristics and including a surgeon report remains unclear, we demonstrated the feasibility of integrating the decision aid into an online pre-surgical assessment in routine clinical care.